Equilibrium indeterminacy with parental altruism - Reichlin, Pietro (Review of economic dynamics, 2019)
Equilibria where altruistic generations are linked via positive bequests are indeterminate and subject to sunspot variables when each individual's utility in non-separable in her own age contingent consumption and sufficiently biased towards old age. This result does not require strong income effects and it applies if individuals select their own savings and bequests by taking the decisions of their offsprings and successors as given. In this case, the equivalence with the Dynastic Equilibria of a Ramsey-type model envisaged in Barro (1974) fails. To help interpreting my results I compare the olg cum altruism model with a canonical non-altruistic olg economy with two goods and age dependent per period utility functions.